2019
DOI: 10.1038/s41598-019-42159-0
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models and strain-dependency of Chédiak-Higashi syndrome-associated neurologic dysfunction

Abstract: Chédiak-Higashi syndrome (CHS) is a lethal disorder caused by mutations in the LYST gene that involves progressive neurologic dysfunction. Lyst -mutant mice exhibit neurologic phenotypes that are sensitive to genetic background. On the DBA/2J-, but not on the C57BL/6J-background, Lyst -mutant mice exhibit overt tremor phenotypes associated with loss of cerebellar Purkinje cells. Here, we tested whether assays for ataxia could measure this obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…[184][185][186] Unfortunately, the neurologic phenotypes displayed by LYST-mutant mice were found to depend on genetic background. 187 Nevertheless, the characterization of Lyst-mutant beige mice indicated that LYST controls phagosomal maturation, triggered as a response to bacterial infection. It specifically regulates the formation of endolysosomal/phagosomal compartments required for the activation of TIR domain-containing adapterinducing interferon β (TRIF) dependent Toll like receptor signaling.…”
Section: Charcot-marie-toothmentioning
confidence: 99%
“…[184][185][186] Unfortunately, the neurologic phenotypes displayed by LYST-mutant mice were found to depend on genetic background. 187 Nevertheless, the characterization of Lyst-mutant beige mice indicated that LYST controls phagosomal maturation, triggered as a response to bacterial infection. It specifically regulates the formation of endolysosomal/phagosomal compartments required for the activation of TIR domain-containing adapterinducing interferon β (TRIF) dependent Toll like receptor signaling.…”
Section: Charcot-marie-toothmentioning
confidence: 99%
“…Recent studies showed that overexpression of GLO1 alleviates MG accumulation, whereas suppression of GLO1 increases MG levels . Given the vital roles of GLO1 and MG in glucose, protein, and fatty acid metabolism, multiple lines of evidence have implicated dysregulation of GLO1 and MG in diabetic complications, aging, carcinogenesis, and behavioral phenotypes, , including anxiety, schizophrenia, depression, and autism.…”
Section: Introductionmentioning
confidence: 99%
“…Guyenet et al developed a valuable composite phenotypic scoring system (CPSS) in 2010 to describe mouse models of cerebellar ataxia measuring: ledge test, hindlimb clasping, gait, and kyphosis ( Guyenet et al, 2010 ). This scoring system was used to distinguish strain-dependent phenotypes in Lyst -mutant mice ( Hedberg-Buenz et al, 2019 ), while a modified version was used in the context of NPC ( Alam et al, 2016 ). A comparison between the different scoring systems is provided in Table 1 .…”
Section: Introductionmentioning
confidence: 99%